THE INFLUENCE OF CULTURALLY RESPONSIVE TEACHING ON THE CRITICAL THINKING ABILITY IN GRADE IV STUDENTS OF MIS YMPI TANJUNG BALAI - Susanti, Eny Yulia; Sari, Suci Perwita (Indonesian Journal of Educational Development (IJED), 2024)
This study aims to determine the influence of the culturally responsive teaching (CRT) approach on the critical thinking ability of fourth grade students in theme 8, subtheme 2, lesson 3 at MIS YMPI Tanjung Balai for the 2022/2023 academic year. This research uses a quasi experimental method, divided into an experimental group and a control group. The population and sample consist of 44 students with class IV A as the experimental class (21 students) and clas IV B as the control class (23 students). The data collection technique used is a critical thinking skills test, adapted to the students cognitive level according to Bloom’s Taxonomy (C4-C6). The data analysis technique employed is the independent sample t-test to determine whether there is an effect of using the culturally responsive teaching (CRT) approach on students critical thinking ability. Based on the research results, the average score for the experimental class was 81,13 while the control class average 65,40 as evidenced by the students post test results. Hypothesis testing showed a Sig. (2-tailed) result of 0.000 < 0.05, indicating that Ha is accepted, and H0 is rejected. This means that there is a significant influence of culturally responsive teaching (CRT) on the critical thinking ability of fourth grade students at MIS YMPI Tanjung Balai.